Marketing and Business Strategies Based on the Creative Economy in Efforts to Improve the Competitiveness of MSME Players - Syam, Shofiana; Daga, Rosnaini; Susanto, Setya Ega; Salam, Karta Negara (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aimed to analyze the impact of strategic management, specifically marketing and creative-economy-based development strategies, on the competitiveness of culinary enterprises in Makassar. A quantitative research design was employed, using a survey to collect primary data from a representative sample selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling to evaluate structural relationships and test the research hypotheses. The results indicated that creative economy-based marketing strategies had a significant positive effect on competitiveness. Furthermore, development strategies based on the creative economy were found to contribute even more significantly to enterprises' ability to strengthen their competitive position in the local market. These findings emphasize the necessity of adopting innovative and adaptive business models to thrive amid market dynamics. This study provides a solid foundation for enterprise actors and policymakers to enhance creative promotion and strategic development, ensuring long-term business sustainability and competitive advantage.